Identification of the Impacts of Climate Changes and Human Activities on Runoff in the Jinsha River Basin, China. (20th July 2017) - Liu, Xiaowan; Peng, Dingzhi; Xu, Zongxue
Abstract : Quantifying the impacts of climate changes and human activities on runoff has received extensive attention, especially for the regions with significant elevation difference. The contributions of climate changes and human activities to runoff were analyzed using rainfall-runoff relationship, double mass curve, slope variation, and water balance method during 1961–2010 at the Jinsha River basin, China. Results indicate that runoff at upstream and runoff at midstream are both dominated by climate changes, and the contributions of climate changes to runoff are 63%~72% and 53%~68%, respectively. At downstream, climate changes account for only 13%~18%, and runoff is mainly controlled by human activities, contributing 82%~87%. The availability and stability of results were compared and analyzed in the four methods. Results in slope variation, double mass curve, and water balance method except rainfall-runoff relationship method are of good agreement. And the rainfall-runoff relationship, double mass curve, and slope variation method are all of great stability. The four methods and availability evaluation of them could provide a reference to quantification in the contributions of climate changes and human activities to runoff at similar basins in the future.